2006
DOI: 10.1007/s11240-005-9021-y
|View full text |Cite
|
Sign up to set email alerts
|

Plant regeneration via somatic embryogenesis from in vitro tissue culture in two Tunisian Cucumis melo cultivars Maazoun and Beji

Abstract: Hypocotyl, cotyledon and zygotic embryo explants from two Tunisian Cucumis melo L. cultivars Beji and Maazoun, cultured on the MS medium added with 2,4-D (0.25-1 mg l )1 ) and BA (0.10-0.50 mg l )1 ), produce calluses with somatic embryos after 3 weeks of culture. For Beji c.v. the highest percentage (62.50%) of embryogenesis was observed for cotyledons. The average embryo number per callus was 10.40. Embryogenesis induction for zygotic embryos reached 33.50% with 29 embryos per callus. The embryogenesis abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 9 publications
(7 reference statements)
1
8
0
Order By: Relevance
“…In the present study asynchronous development of somatic embryogenesis have been reported earlier in some melon species like Cucumis melo (Akasaka Kennedy et al 2004;Rhimi et al 2006;Kageyama et al 1991). Several other investigators have been reported somatic embryogenesis and plant regeneration studies from various explants of cucurbitaceous species like Cucurbita pepo and Cucurbita moschata (Noel et al 1992;Usman et al 2011).…”
Section: Effect Of 24-d Alone or In Combination With Bap On Inductiosupporting
confidence: 77%
“…In the present study asynchronous development of somatic embryogenesis have been reported earlier in some melon species like Cucumis melo (Akasaka Kennedy et al 2004;Rhimi et al 2006;Kageyama et al 1991). Several other investigators have been reported somatic embryogenesis and plant regeneration studies from various explants of cucurbitaceous species like Cucurbita pepo and Cucurbita moschata (Noel et al 1992;Usman et al 2011).…”
Section: Effect Of 24-d Alone or In Combination With Bap On Inductiosupporting
confidence: 77%
“…Subsequently, many transgenic melon plants have been produced (Rhimi et al, 2006;Ren et al, 2012). However, the transformation efficiency in melon is not high enough.…”
Section: Discussionmentioning
confidence: 99%
“…Although melon is susceptible to Agrobacterium infection and responsive to regeneration from explants derived from the cotyledon (Dirks and van Buggenum, 1989) and callus (Moreno et al, 1985), the transformation regeneration frequency varies widely among cultivars (Galperin et al, 2003;Akasaka-Kennedy et al, 2004;Rhimi et al, 2006;Hao et al, 2011) and sources of explants (Fang and Grumet, 1990;Guis et al, 2000;Ren et al, 2012). Moreover, in melon transformation, a high frequency of tetraploids and false-positive regenerants are common phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Melon is susceptible to Agrobacterium infection and responds to regeneration from explants derived from both cotyledon (Dirks and van Buggenum, 1989) and callus (Moreno et al, 1985), although the frequency of transformation regeneration varies widely among cultivars (Galperin et al, 2003;Akasaka-Kennedy et al, 2004;Rhimi et al, 2006;Hao et al, 2011;Akbari et al, 2013) and sources of explants (Fang and Grumet, 1990;Gray et al, 1993;Ren et al, 2012Ren et al, , 2013Bezirganoglu et al, 2013;Zhang et al, 2014;Zhang and Luan, 2015). However, the genes responsible for regeneration of melon continue to be poorly understood.…”
Section: Introductionmentioning
confidence: 99%